Compatibility study of NaN5 with traditional energetic materials and HTPB propellant components. Issue 4 (1st October 2020) - Yao, Yu-Yang; Zhou, Xin –Li; Lin, Qiu-Han; Lu, Ming
ABSTRACT: Nitrogen-rich and poly-nitrogen energetic materials have the advantages of high density, high formation enthalpy, and environmentally friendly as new energetic materials. Among them, cyclo-N5 − is one of the most representative ionic nitrogen compounds. However, at present, the studies are mainly in the field of synthesis. This study mainly explores the compatibility of NaN5 with traditional energetic materials, hydroxy-terminated polybutadiene (HTPB), and ammonium perchlorate (AP). The compatibility is an important parameter to evaluate the safety and reliability of propellants. Therefore, AP, cyclotetramethylenetetranitramine (HMX), cyclotrimethylenetrinitramine (RDX), hexanitrohexazaisowurtzitane (CL-20), HTPB were selected to study the compatibility of NaN5 in the means of differential scanning calorimetry (DSC). The results show that NaN5 /AP, NaN5 /HMX, NaN5 /RDX, NaN5 /CL-20 have good compatibility, whereas NaN5 /HTPB exhibits moderate compatibility.